2011
DOI: 10.5194/acp-11-12169-2011
|View full text |Cite
|
Sign up to set email alerts
|

ACE-FTS measurements of trace species in the characterization of biomass burning plumes

Abstract: Abstract. To further our understanding of the effects of biomass burning emissions on atmospheric composition,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 35 publications
6
58
1
Order By: Relevance
“…Table 2 compares our derived emission ratio for HCOOH to previous satellite, aircraft, and ground measurements of formic acid emission ratios for boreal biomass burning. Our HCOOH emission ratio is slightly lower than the ratio of 0.38% ± 0.06% derived from ACE-FTS observations [31], possibly due to the fact that a limb-sounder like ACE is more sensitive to plumes that reach high altitudes; this type of plume is more common over more flaming fires since fire power output peaks during flaming combustion [4]. Table 2 shows that our value is similar to the emission ratios for HCOOH derived from aircraft and ground studies, with the exception of the value of 3.7% ± 2.0% reported for Canadian forests by Lefer et al [60], which is about a factor of 10 higher than the average value for boreal biomass burning in the review of Akagi et al [3].…”
Section: Hcooh Retrievalmentioning
confidence: 51%
See 2 more Smart Citations
“…Table 2 compares our derived emission ratio for HCOOH to previous satellite, aircraft, and ground measurements of formic acid emission ratios for boreal biomass burning. Our HCOOH emission ratio is slightly lower than the ratio of 0.38% ± 0.06% derived from ACE-FTS observations [31], possibly due to the fact that a limb-sounder like ACE is more sensitive to plumes that reach high altitudes; this type of plume is more common over more flaming fires since fire power output peaks during flaming combustion [4]. Table 2 shows that our value is similar to the emission ratios for HCOOH derived from aircraft and ground studies, with the exception of the value of 3.7% ± 2.0% reported for Canadian forests by Lefer et al [60], which is about a factor of 10 higher than the average value for boreal biomass burning in the review of Akagi et al [3].…”
Section: Hcooh Retrievalmentioning
confidence: 51%
“…The large pressure range of TES sensitivity to HCOOH may also contribute to the low correlation of HCOOH with CO. It is worth noting that the ACE-FTS observations of HCOOH within boreal biomass burning plumes showed a much higher r 2 value (0.86), likely due to the fact that the higher vertical resolution of limb retrievals means that ACE is better able to separate the different vertical layers of the plume which are averaged together by nadir-viewing sounders like TES and IASI [31]. Table 2 compares our derived emission ratio for HCOOH to previous satellite, aircraft, and ground measurements of formic acid emission ratios for boreal biomass burning.…”
Section: Hcooh Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from these preliminary studies precipitated interest in the retrieval of additional pyrogenic organic species such as ethene (C 2 H 4 ), propyne (C 3 H 4 ), formaldehyde (H 2 CO), acetone (C 3 H 6 O), and peroxyacetylnitrate -abbreviated as PAN (CH 3 COO 2 NO 2 ) -and were the first reported detections of these species using infrared solar occultation spectroscopy from satellites . Most recently, ACE-FTS was successfully used to demonstrate its ability to characterize biomass burning emissions from distinct fuel types and follow their chemical evolution as the plumes age in the troposphere (Tereszchuk et al, 2011). The results of this investigation indicated that space-borne measurements of biomass burning emissions from different ecosystems can be differentiated by their unique chemical composition and that the formation and destruction of pyrogenic trace species within biomass burning plumes can be monitored, thus forming the basis for this more extensive work.…”
Section: K a Tereszchuk Et Al: Ace-fts Observations Of Pyrogenic Tmentioning
confidence: 99%
“…In addition to these species, CH 3 OH and H 2 CO have been measured by the ACE-FTS globally (Dufour et al, , 2009) and in biomass burning plumes over northern high latitudes Tereszchuk et al, 2011Tereszchuk et al, , 2013 and in the Southern Hemisphere .…”
Section: Ace-fts Measurementsmentioning
confidence: 99%